Canadian Gallup Poll, April 1987, #520_2 - Gallup Canada (Borealis, 2019)
This Gallup poll seeks the opinions of Canadians, on predominantly social and lifestyle issues. The questions ask opinions on smoking, a potential ban on the sale of tobacco, the Charter of Rights and Freedoms and pollution. There are also questions on other topics of interest such as knowledge of the Northwest passage, religious habits and Canada's involvement in the high tech industry. The respondents were also asked questions so that they could be grouped according to geographic, political and social variables. Basic demographic variables are also included.